SEKOPER MARLENA” SEKOLAH PEREMPUAN MARLENA UPAYA MEWUJUDKAN PEREMPUAN MADURA BERDIKARI MENUJU SMART WOMEN’S VILLAGE DI DESA SEMBILANGAN-BANGKALAN - Ira Damayanti; Luluk Fauziyah Januarti; Amelia Afitri; Adinda Nindia Candra Putri Amirullah; Abdurrahman Wahid; Ananda Yulia Mayasari Azis; Ryan Dwipa; Qurratul Aini; Muhammad Maimunun Mubarok; Moh Ma'ruf; Qurrotul Ainiyah; Nurul Mauidhotul Hasanah; Zahratul Isnaini; Muhammad Farhan (STIKES NGUDIA HUSADA MADURA, 2023)
Women are part of society and are expected to contribute to aspects of development. This Women's School was built for Sembilangan village women who have not been exposed to the safety and comfort of women in the village, women's ability to take care of the family, women's knowledge about the family, knowledge and attitudes towards the role of women in village development, mastery of information technology to increase capacity and identify the level of mastery of women. village women regarding economic resources and natural resources that can be utilized to improve the quality of themselves and their families. The planned solution to resolve this problem includes providing education about women. This program is packaged under the title Sekoper Marlena (Marlena Women's School) as an effort to increase the knowledge of Madurese women in Sembilangan Village towards a Smart Women's Village. This education is carried out regularly using lecture, fun game, small group discussion, project base learning methods, using curriculum references that have been planned according to the needs and expectations of Sembilangan Village regarding the high female population in the village so that village women are useful. we provide learning assistance with the curriculum, namely material on the role of women in village development, material on women's safety against the risk of harassment. Overcoming the problem of low knowledge of the majority of women, we provide learning guidance with the following curriculum; Material on understanding the concept of family, Basic women's material (gender perspective), Women's material from Sekoper Marlena (KEPO) Reproductive and Sexual Health, Material on women preventing early marriage, Material on women's readiness to become mothers, Material on creative women in fulfilling family nutrition and nourishment (Smart Moms - MP-Asi), Parenting material for mothers and children, Material for women's safety against the risk of sexual harassment, Material for Marlena's Sekoper creative use of local food, Material for Marlena's Sekoper empowering families towards a Smart Woman Village, Material for mastering information technology in the use of social media to increase women's knowledge and media for women's creativity (Barcode Marlena Caring), Material for Marlena's Suitcase Happy prevention of psychosocial stress for mothers, Overcoming the problem of limited local food management capabilities, we provide assistance to provide innovation in management as an effort to improve the economy by training in the management of SUMI (Economic Inspiration breadfruit) .